A Case Study: The Feminist and Cultural Contribution to Transpersonal Experience - Olak, Pankrasius (SOLUTION, Journal of Counseling and Personal Development, 2019)
Indeed feminist spirituality belongs to the woman. However, a woman is not automatically attune with feminist spirituality if she is not aware of and open to. This case study presents that man can experience the feminist spirituality when he is open to that spirit. Because of the awareness and openness, the hidden qualities of his anima side is connected and transformed by the feminist spirituality of the participants of this study. Therefore, researcher believe that anyone who is aware of her and his feminist?s spiritual qualities can be connected with the spirit within and around that lead toward spiritual integration that bear fruit of transformation.